A new species of Ogyrides (Decapoda, Caridea, Ogyrididae) from Kuwait - De Grave, S; Al-Kandari, M; Anker, A (Brill Academic Publishers, 2020)
A new species of telescope shrimp, Ogyrides sindibadi sp. nov. is described from Kuwait. The new species is morphologically similar to O. striaticauda Kemp, 1915, originally described from Chilka Lake (India), but can be distinguished by the shape of the scaphocerite, the much longer dactylus of the third pereiopod, as well as the shape of the distal margin of the telson.